Race, fitness-to-practice and the experience of trainee educators - Celia Clarke (Fields, 2022)
This study examines the reasons behind Black, Asian and Minority Ethnic (BAME) students’ over-representation within fitness-to-practice (FTP) processes at a university in the north of England. Referrals to FTP are intended to rectify the underperformance of students, acting as a workplace misconduct procedure, applied in an education context. The phenomenon itself replicates trends of racial disadvantage across education and the workplace. Some suggested causes for these trends include capital, racial discomfort and structural inequality discussed in the literature review. In this study, the experiences of BAME students on placement in education settings are examined to provide insights into the disparity in FTP referrals, using a phenomenological approach. This involved semi-structured interviews to capture subjective first-person accounts from the target sample. These were evaluated using thematic analysis, and the findings were considered using Critical Race Theory (CRT) as a lens.The findings demonstrated two opposing accounts that were united by their conception of racial identity. The research found that BAME students’ placement experiences may be in response to an intersectional convergence of race and the status of the role they occupy within the placement. A clear link between FTP and placement experiences could not be established, but the CRT perspective points to issues around racism, white neutrality and supremacy active in BAME students’ placement settings.